2017
DOI: 10.1111/apt.13913
|View full text |Cite
|
Sign up to set email alerts
|

Review article: dose optimisation of infliximab for acute severe ulcerative colitis

Abstract: Uncontrolled studies suggest a benefit for infliximab dose optimisation in patients with acute severe UC. A randomised controlled trial in acute severe UC patients comparing a personalised infliximab dose-optimisation strategy with conventional dosing is a research priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 82 publications
(182 reference statements)
1
57
0
9
Order By: Relevance
“…This may be attributed to the severity of UC in the pediatric population, resulting in a more systemic effect, as reflected in a much higher proportion of pediatric patients with pancolitis compared with adult patients with UC . Despite the fact that UC is considered a mucosal disease, restricted to the large bowel, the inflammatory burden in patients with pancolitis is extremely high and often requires intensification of anti‐inflammatory treatment . Thus, it should not be surprising that iron and zinc deficiencies remain high in pediatric patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the severity of UC in the pediatric population, resulting in a more systemic effect, as reflected in a much higher proportion of pediatric patients with pancolitis compared with adult patients with UC . Despite the fact that UC is considered a mucosal disease, restricted to the large bowel, the inflammatory burden in patients with pancolitis is extremely high and often requires intensification of anti‐inflammatory treatment . Thus, it should not be surprising that iron and zinc deficiencies remain high in pediatric patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Parece racional sugerir, por lo previamente expuesto, que frente a una CUg sea necesario modificar el esquema de inducción ya sea acortando los intervalos de las dosis (0, 1 y 4 semanas) y/o aumentando la dosis del biológico (10 mg/kg) 12 .…”
Section: Discussionunclassified
“…Aunque mayores dosis sean utilizadas, un clearance aumentado del fármaco afectará los niveles hacia el final de cada intervalo 23,24 . En nuestra paciente decidimos utilizar un esquema acelerado (0, 1 y 4 semanas) con aumento de la dosis administrada (10 mg/kg) dado la severidad clínica y endoscópica 12 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The 90-day colectomy rate was 47% in the dose-intensified group versus 12.5% in the standard induction group (p=0.01). A recent review of all cohort and case–control studies suggests a benefit for IFX dose optimisation in at least 50% of patients with ASUC with an 80% reduction in colectomy rates 74. However, a recent retrospective multicentre study and meta-analysis involving seven studies (181 patients receiving accelerated IFX and 436 receiving standard IFX) found no significant differences in short- or long-term outcomes between the two 75…”
Section: Medical Managementmentioning
confidence: 99%